UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS III DENGAN MENERAPKAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH PADA MATERI PECAHAN SEDERHANA - Sintia Sri Wahyuni; Aries Tika Damayani (Jurnal Prasasti Ilmu, 2025)
The aim of this research is to improve the learning outcomes of third grade elementary school students by adopting the "make a match" pair card matching technique to learn simple fractions. Considering the findings from initial observations, 55% of class III students at SD Negeri 09 Batu Bulek showed that their mathematics learning results were below the KKTP. One of the research methodologies used in this research is classroom action research. The assessment process is carried out in two cycles, with one meeting each cycle consisting of preparation, implementation, observation and reflection. Through the use of test tools in the form of essay test questions, data collection methods were implemented. Quantitative data, especially averages and pass percentages, are used in data analysis techniques. The pre-cycle average was 55%, cycle I was 81% and cycle II was 93%, according to research findings. Therefore, the results of grade 3 mathematics learning at SD Negari 09 Batu Bulek, North Lintau Buo District, Tanah Datar Regency can be improved with a make a match type cooperative model.